Multiple internal controls enhance reliability for PCR and real time PCR detection of Rathayibacter toxicus - Mohammad Arif (Nature Portfolio, 2021)
Abstract Rathayibacter toxicus is a toxigenic bacterial plant pathogen indigenous to Australia and South Africa. A threat to livestock industries globally, the bacterium was designated a U.S. Select Agent. Biosecurity and phytosanitary concerns arise due to the international trade of seed and hay that harbor the bacterium. Accurate diagnostic protocols to support phytosanitary decisions, delineate areas of freedom, and to support research are required to address those concerns. Whole genomes of three genetic populations of R. toxicus were sequenced (Illumina MiSeq platforms), assembled and genomic regions unique to each population identified. Highly sensitive and specific TaqMan qPCR and multiplex endpoint PCR assays were developed for the detection and identification of R. toxicus to the population level of discrimination. Specificity was confirmed with appropriate inclusivity and exclusivity panels; no cross reactivity was observed. The endpoint multiplex PCR and TaqMan qPCR assays detected 10 fg and 1 fg of genomic DNA, respectively. To enhance reliability and increase confidence in results, three types of internal controls with no or one extra primer were developed and incorporated into each assay to detect both plant and artificial internal controls. Assays were validated by blind ring tests with multiple operators in three international laboratories.